A study on critical failure factors for implementation of sustainable Lean Six Sigma from Indian manufacturing industries perspective using BWM technique - Kumar, Sandeep; Kumar, Ravinder; Phanden, Rakesh Kumar; Kumar, Ajay; Bala, Jagadeesh; Bharath Kumar, S.; Giri, Jayant; Sathish, Rao U.; Agrawal, Ashish; Vishwanatha, H. M. (Frontiers in Mechanical Engineering, 2024)
The adoption of Lean Six Sigma has become increasingly widespread in manufacturing industries worldwide. It is a powerful methodology for optimizing operational efficiency and quality, leading to increased productivity, reduced costs, and higher customer satisfaction. However, implementing LSS effectively, especially in Indian manufacturing sectors striving for sustainability, presents significant challenges. In this paper, the authors have presented the critical factors that impede the successful integration of sustainable Lean Six Sigma practices within the Indian manufacturing landscape. Through a systematic review of existing literature and empirical studies, authors have identified the eighteen failure factors. To prioritize these factors, authors have employed the Best Worst Method (BWM), a decision-making tool that aids in ranking factors based on their importance and impact. It is a multi-criterion decision-making (MCDM) methodology to solve different types of fact-based decision–making problems. This method involves initially identifying the best (most important) and worst (least important) factors, followed by pairwise comparisons to determine their relative significance. Results depict that “Failure of leadership to inspire and motivate”, “Lack of well-defined framework for executing initiatives”, and “High implementation cost and poor estimation of cost” are three top-level critical failure factors.